Gut Pathobiont–Derived Outer Membrane Vesicles Drive Liver Inflammation and Fibrosis in Primary Sclerosing Cholangitis–Associated Inflammatory Bowel Disease - Dorner, Heidrun; Stolzer, Iris; Mattner, Jochen; Kaminski, Sophie; Leistl, Sofia; Edrich, Lisa-Maria; Schwendner, Raphael; Hobauer, Julia; Sebald, Adrian Thomas Erwin; Leikam, Stefanie; Gonzalez Acera, Miguel; Düll, Miriam; et al. (Gastroenterology, 2024)
Background & Aims: Primary sclerosing cholangitis (PSC), often associated with inflammatory bowel disease (IBD), presents a multifactorial etiology involving genetic, immunologic, and environmental factors. Gut dysbiosis and bacterial translocation have been implicated in PSC-IBD, yet the precise mechanisms underlying their pathogenesis remain elusive. Here, we describe the role of gut pathobionts in promoting liver inflammation and fibrosis due to the release of bacterial outer membrane vesicles (OMVs). Methods: Preclinical mouse models in addition to ductal organoids were used to acquire mechanistic data. A proof-of-concept study including serum and liver biopsies of a patient cohort of PSC (n = 22), PSC-IBD (n = 45), and control individuals (n = 27) was performed to detect OMVs in the systemic circulation and liver. Results: In both preclinical model systems and in patients with PSC-IBD, the translocation of OMVs to the liver correlated with enhanced bacterial sensing and accumulation of the NLRP3 inflammasome. Using ductal organoids, we were able to precisely attribute the pro-inflammatory and pro-fibrogenic properties of OMVs to signaling pathways dependent on Toll-like receptor 4 and NLRP3–gasdermin-D. The immunostimulatory potential of OMVs could be confirmed in macrophages and hepatic stellate cells. Furthermore, when we administered gut pathobiont–derived OMVs to Mdr2–/– mice, we observed a significant enhancement in liver inflammation and fibrosis. In a translational approach, we substantiated the presence of OMVs in the systemic circulation and hepatic regions of severe fibrosis using a PSC-IBD patient cohort. Conclusions: This study demonstrates the contribution of gut pathobionts in releasing OMVs that traverse the mucosal barrier and, thus, promote liver inflammation and fibrosis in PSC-IBD. OMVs might represent a critical new environmental factor that interacts with other disease factors to cause inflammation and thus define potential new targets for fibrosis therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Bacterial Extracellular Vesicle; Hepatic Inflammation; Inflammasome; PSC-IBD